VIRTUAL REALITY TRENDS IN EDUCATIONAL SIMULATION: PERSPECTIVES, CHALLENGES, AND CURRENT PRACTICES - L.Virginayoga Hignasari (International Journal of Teaching and Learning, 2024)
Virtual Reality (VR) provides an immersive and interactive experience, allowing students to engage more deeply in the learning process. This experience can improve understanding and retention of information because students can feel and interact directly with learning material. VR technology enables personalized learning according to each student's needs and learning pace. This helps accommodate a variety of learning styles and abilities, providing a more inclusive experience. Virtual Reality has great potential to revolutionize education through immersive and interactive simulations. However, challenges such as cost, availability of quality content, and health concerns need to be overcome for this technology to be adopted more widely and effectively. Current practice shows that with the right approach, Students in a range of academic areas can benefit from creative and relevant learning experiences that virtual reality can offer. Virtual reality (VR) has demonstrated significant promise in enhancing student comprehension and learning. VR can be a useful tool for developing creative and interesting learning experiences for students if current techniques are put into practice and present problems are overcome.